PENGARUH HARGA DAN BIAYA TERHADAP PENDAPATAN PETANI KELAPA SAWIT PADA KUD CINTA DAMAI DI KECAMATAN TAPUNG HILIR - Wahab, Wirdayani; Pamungkas, Putra (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
The purpose of the study was to determine the effect and cost of the income of oil palm farmers at the KUD Â Cinta DamaiÂ in Tapung Hilir District. The method in this study uses quantitative descriptive method. The sample in this study were 86 people from 636 farmers using random samples. In this study using hypothesis testing consisting of F test, and t test. Based on the results of the F test, it is evident that prices and costs are significant to farmers' income, folding with Fcount values greater than Ftable (50,569> 3,11). Based on the F test results it is proven that prices and costs have a significant effect on farmer income, indicated by the value of Fcount greater than Ftable (50,569> 3,11). Based on the t test it is proven that the price has a significant effect on farmer income indicated by a tcount greater than t table (9,010> 1,989) and the cost has a significant effect on the income of oil palm farmers in KUD Cinta Damai indicated by a tcount greater than ttable (2,068> 1,989)